Reduced Donaldson-Thomas invariants and the ring of dual numbers - Oberdieck, Georg; Shen, Junliang (Proceedings of the London Mathematical Society, 2019)
Let A be an abelian variety. We introduce A-equivariant Grothendieck rings and A-equivariant motivic Hall algebras, and endow them with natural integration maps to the ring of dual numbers. The construction allows a systematic treatment of reduced Donaldson-Thomas (DT) invariants by Hall algebra techniques. We calculate reduced DT invariants for K3×E and abelian threefolds for several imprimitive curve classes. This verifies (in special cases) multiple cover formulas conjectured by Oberdieck-Pandharipande and Bryan-Oberdieck-Pandharipande-Yin.
Online veröffentlicht: 2. August 2018
Gesehen am 14.01.2025